Latest findings challenge behavioural approaches to the management of antipsychotic-induced weight gain - Steve Kisely; Dan Siskind; Helene Speyer (BJPsych Open)
Obesity is a major health problem among people with severe mental illness, linked to increased risk of chronic diseases and reduced life expectancy. This is attributable to a combination of factors, including lifestyle, social circumstances, medication side-effects and the illness itself. Second-generation antipsychotics are particularly associated with weight gain, affecting treatment adherence, symptoms and quality of life.